Hubungan Jumlah Daun terhadap Jumlah Polong, Berat Polong, dan Jumlah Biji Edamame di Tanah Berpasir - Nur Halimah; Pienyani Rosawanti; Hariyadi; Muh. Azhari (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
This study aims to study the correlation between the variables of the number of leaves to the number of pods, the number of seeds per pod, and the weight of pods in edamame plants (Glycine max L. Merrill). Edamame is a type of vegetable soybean that is harvested when the pods are still young, originating from Japan, and is widely known as a healthy snack. This study uses regression and correlation analysis to examine the extent to which the number of leaves affects the components of plant generative results. This study was conducted from September 2024 to January 2025 at the experimental and research garden of Campus III UMPR, Jl. Ir Soekarno No.I, Palangka Raya City, Central Kalimantan. This study used a randomized design consisting of two factors and the first factor was three levels of chicken manure with three levels of treatment doses of 30, 35, 40 tons ha¹, while the second treatment was the type of biochar with control, rice husks, and empty oil palm bunches. The results showed that the results of the Pearson correlation test for the number of leaves had a positive relationship with the three components of plant yield. The relationship between the number of leaves and the number of pods is classified as moderate, while the number of leaves and the number of seeds and pod weight are classified as weak, the direction shown is one-way or positive